2014
DOI: 10.1242/jeb.099184
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary capacity of upper thermal limits: beyond single trait assessments

Abstract: Thermal tolerance is an important factor influencing the distribution of ectotherms, but we still have limited understanding of the ability of species to evolve different thermal limits. Recent studies suggest that species may have limited capacity to evolve higher thermal limits in response to slower, more ecologically relevant rates of warming. However, these conclusions are based on univariate estimates of adaptive capacity. To test these findings within an explicitly multivariate context, we used a paterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 43 publications
5
79
1
1
Order By: Relevance
“…Furthermore, recent work suggests laboratory maintenance does not have large effects on physiological patterns in Drosophila (Maclean et al ., ). In addition, previous studies (van Heerwaarden & Sgro, ; Blackburn et al ., ) show that populations maintained under these conditions and for similar timescales harbour significant levels of adaptive genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent work suggests laboratory maintenance does not have large effects on physiological patterns in Drosophila (Maclean et al ., ). In addition, previous studies (van Heerwaarden & Sgro, ; Blackburn et al ., ) show that populations maintained under these conditions and for similar timescales harbour significant levels of adaptive genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Using a multivariate approach, Blackburn et al . () further showed that ramping and static knockdown time were not significantly genetically correlated with each other, suggesting that these traits are largely genetically independent.…”
Section: Introductionmentioning
confidence: 94%
“…The response to selection for increased heat tolerance is, however, not only dependent on genetic variation but also on the covariation in the traits under selection (Lynch & Walsh ; Brooks ; Blackburn et al . ). Measuring one component of heat tolerance might therefore over‐ or underestimate the adaptive potential to increase heat tolerance if different components of heat tolerance have a different genetic basis.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations